Efektivitas Pendekatan Contekstual Teaching and Learning terhadap Penguasaan Konsep Akuntansi - Watoni, M.Saipul (Lembaga Yasin AlSys, 2022)
This study aims to determine the effect of the Contextual teaching and learning (CTL) approach with modeling on the mastery of accounting concepts in class XII MA MA NW Keruak. The approach used in this study is a quantitative approach with a quasi-experimental research method that provides treatment to the experimental group, considering that the data in this study do not exist properly, it is necessary to carry out an experiment or treatment to bring up the data. The population in this study were all students of class XII MA NW Keruak with a total sample of 54 students consisting of 2 classes where the experimental class was class XIIa, totaling 29 students, class XIIa. As for the control class, there were 26 students in class XIIb. Data collection techniques using questionnaires/tests, observation and documentation. The results showed that the ability to understand accounting concepts using the contextual teaching and learning (CTL) approach was higher than mastering accounting concepts without using the contextual teaching and learning (CTL) approach with modeling as seen from the average score obtained by students. In this study, the results of the analysis showed that the experimental group achieved a higher average score than the control group. This shows that the use of the contextual teaching and learning (CTL) approach has a positive and significant effect on the mastery of accounting concepts in class XII MA NW Keruak with the rejection rate limit being below or smaller than the t count or 6.28> 2.08 which means shows that there is a significant influence on the mastery of accounting concepts by using a contextual teaching and learning approach.